Tecnologia LoRa para otimização do manejo da irrigação em morangueiro - Dal Magro, Samuel Zottis (2025)
The accelerated growth of the Internet of Things (IoT) market has driven the development of new technologies in the areas of microelectronics, wireless communication, and microprocessors. However, limited internet connectivity in rural areas and the high cost of traditional irrigation monitoring systems restrict producers' access to these technologies. Thus, we sought to develop a low-cost, low-energy smart irrigation system using LoRa technology, capable of measuring and sending data on agrometeorological and substrate variables efficiently, improving irrigation management, production, and quality of strawberry fruits. SHT20, SKU SEN0193 V2.0, and DS18b20 sensors were calibrated and tested under real-world conditions, with data stored in InfluxDB and visualized via Grafana. The hardware, consisting of Arduino Pro Mini with LoRa transceivers, sensors, and servo-controlled valves, was used for irrigation management. Finally, an experiment was conducted in a randomized block design with four replications in a factorial scheme, evaluating four irrigation levels and six biostimulants. The system made it possible to measure and transmit accurate air temperature and humidity data using the SHT20 sensor, provided that the sensor was protected against direct solar radiation and wind. The DS18b20 sensor showed excellent accuracy in measuring substrate temperature, while the SKU V2.0 capacitive sensor was efficient in measuring substrate moisture. However, it was necessary to individually calibrate the sensors for greater reliability in irrigation management. Less deficient irrigation levels, with a volume greater than 239 mL of water per plant per day, provided greater fruit production and a better total soluble solids/titratable acidity (TSS/TTA) ratio. LoRa technology, together with InfluxDB and Grafana, proved to be efficient for monitoring the microclimate in the strawberry greenhouse, allowing realtime monitoring, assisting in irrigation management and automation.